QUARTER LIFE CRISIS DARI SUDUT PANDANG TEOLOGI BIBLIKA MATIUS 6:25-34 - Sakai, Eklis; Sugiarto, Jimmy; Yosua Sualang, Farel (Misioner, 2023)
At the age of 18-29, humans will face a quarter-life crisis, which is a phase of crisis during the transition to early adulthood. During this period, individuals may experience a loss of confidence in their future life. The quarter-life crisis requires serious attention from pastoral caregivers. This research aims to discover the principles of Biblical Theology in Matthew 6:25-34 to overcome the quarter-life crisis. Using the Pastoral Thematic method, this article finds that there are principles that can be applied in dealing with the quarter-life crisis. There are four reasons underlying these findings: Firstly, God as the center of devotion, creator, sustainer, and provider. Secondly, Anthropology that states the value of human life before God and humans' dependence on God's provision. Thirdly, Faith formed from understanding how much God loves humans and how humans live under God's provision. Fourthly, the Kingdom of God, which sets the standard for the lives of believers, where God is the King who will fulfill all the needs of His subjects. These principles address the tensions faced by early adults when confronting the quarter-life crisis.